Multi-drug resistant Enterococcus faecium in late-onset keratitis after deep anterior lamellar keratoplasty: A case report and review of the literature. Issue 37 (September 2019) - D'Oria, Francesco; Galeone, Alessandra; Pastore, Valentina; Cardascia, Nicola; Alessio, Giovanni
Abstract: Rationale: Interface keratitis after lamellar keratoplasty is one of the causes of graft failure. We report the first case of microbiologically proven Enterococcus faecium infection following deep anterior lamellar keratoplasty (DALK) and review the available literature. Patient concerns: A 37-years-old Caucasian man presented with pain, redness and severe vision loss in his right eye. Five weeks before, he underwent DALK using the FEMTO LDV Z8 in the same eye for the surgical correction of keratoconus. Diagnoses: Upon presentation, slit-lamp biomiscroscopy revealed corneal graft edema with multiple infiltrates located in the graft-host interface. Interventions: Therapeutic penetrating keratoplasty (PKP) was carried out in addition with cultures of the donor lenticule removal. Laboratory results isolated a multi-resistant Enterococcus faecium interface infection. According to the antibiogram, the patient was treated with systemic Tigecycline and Linezolid for 7 days. Outcomes: During the following weeks, clinical features improved over time and no signs of active infection were visible seven months postoperatively. Lessons: Early PKP showed to be a good therapeutic option with great anatomic and functional outcomes.